A Model Lesson Plan for Teaching Reading Comprehension Skills to Secondary Level English Learners - Rai, Ichchha Purna (Rupantaran: A Multidisciplinary Journal, 2026)
A lesson plan is the backbone of effective teaching at any level. However, many secondary-level English teachers find it difficult to design effective lesson plans while teaching English as a foreign language. The main aim of this article is to provide practical guidelines for teachers on designing and implementing effective lesson plan in English language classrooms, particularly teaching reading comprehension using the Presentation, Practice and Production (PPP) framework. Adopting the qualitative, design-based methodology, the study is based entirely on secondary sources to design the lesson plan. The findings highlight the key components of a lesson plan, including objectives, materials, activities and evaluation which engage students, promote creativity and facilitate effective learning. This study concludes that a well-structured lesson plan always engages students, provides clarity, and facilitates learning. Finally, this article contributes a model lesson plan for secondary English teachers, particularly for teaching reading comprehension.